Electrically induced coloration of polymer-stabilized cholesteric liquid crystal films with broadband reflection capability for smart windows. (July 2022) - Zhang, Huimin; Liu, Jie; Zhao, Xiangrong; Gao, Jianjing; Ma, Cheng; Zhao, Yang; Yao, Ruijuan; Miao, Zongcheng; Shen, Wenbo
Abstract: In this work, a novel approach to realizing the electrically induced coloration of polymer-stabilized cholesteric liquid crystal (LC) films with broadband reflection capability for smart windows was reported. Only starting common materials and an established preparation method were used. The polymer-stabilized cholesteric LC films with broadband reflection capability were prepared via the method of polymerization-induced pitch gradient. After doping with a commercial ionic liquid which served as the supporting electrolyte in the system, the initial broadband reflection capability of the polymer-stabilized cholesteric LCs film was not damaged, and the film can change into a colored state from a colorless state under a low direct current (DC) voltage. The color of the polymer-stabilized cholesteric LCs also can gradually disappear after the removal of the field despite the slow response rate. The as-prepared polymer-stabilized cholesteric LCs in this work not only can be applied in the energy-saving smart windows and thermal management for buildings, but also presented the performance of electrically induced coloration under a low voltage. This work is expected to provide a creative approach for the preparation of electrochromic energy-saving smart windows. Highlights: A new approach to realizing the electrically induced coloration of polymer-stabilized cholesteric films is reported. Only starting common materials and an established preparation method are used. After doping with an ionic liquid, the film can change into a colored state from a colorless state under a DC voltage. The broadband reflection capability of the cholesteric film is not damaged by the ionic liquid. The as-prepared film can be applied in energy-saving smart windows and thermal management for buildings.